On the brink of extinction: two new species of Anomaloglossus from French Guiana and amended definitions of Anomaloglossus degranvillei and A. surinamensis (Anura: Aromobatidae) - Fouquet, Antoine; Vacher, Jean-Pierre; Courtois, Elodie A.; Villette, Benoit; Reizine, Hugo; Gaucher, Philippe; Jairam, Rawien; Ouboter, Paul; Kok, Philippe J. R. (Zootaxa, 2018)
A large portion of the amphibian species occurring in Amazonia remains undescribed. A recent study on species delineation in Anomaloglossus, a genus endemic to the Guiana Shield, demonstrated the existence of two undescribed species previously identified as A. degranvillei, which we describe herein. In addition to divergence at the molecular level, these two new taxa are also distinguished by subtle morphological characters and substantial differences in the advertisement calls (note length, dominant frequency, note structure). One species occurs in the hilly lowlands of north-eastern French Guiana and is mainly distinguished from its closest relatives by a small body size (15.9–18.8 mm in males) and by vocalisations characterized by the emission of short notes of 0.09 s on average. The other species is only known from the Itoupé Massif in southern French Guiana and is mainly distinguished from its closest relatives by a moderate body size (19.4–20.4 mm in males) and by vocalisations characterized by the emission of long notes of 0.23 s on average. We also provide amended definitions for two previously described species in the A. degranvillei species group: A. degranvillei, which is endemic to a few massifs in central French Guiana, and A. surinamensis, which is distributed throughout Suriname and French Guiana. The new species described here and A. degranvillei have very narrow ranges within French Guiana and seem to have rapidly declined during the last decade. Therefore, we suggest A. degranvillei and A. dewynteri to be considered as “Critically Endangered” and A. blanci as “Vulnerable” according to the IUCN standards.